Decoding the chemical signatures of Chinese specialty honeys via multi-omics approaches: A review - Xintong Hou; Benyan Tang; Longfei Chen; Mohamed G. Sharaf El-Din; Liuwei Zhao; Xiaofeng Xue; Liming Wu; Daniel Granato; Kai Wang (Trends in Food Science & Technology, 2026)

RT-BFE network: A lightweight deep learning model for real-time beef freshness evaluation and edge devices deployment - Weidong Xu; Yingchao He; Liming Que; Caitian Tang; Jiaheng Li; Chunxu Zhang; Qirong Dong; Huadong Sheng; Pengpeng Liu; Wenjun Wang; Donghong Liu (Computers and Electronics in Agriculture, 2026)

Retraction Note: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2026)

Multi-scale pore network approaches for predicting collector efficiency of colloids across a wide density range in soil hydrologic systems - Dantong Lin; Scott Alan Bradford; Yazhou Cao; Minpeng Tang; Baoqing Zhang; Liming Hu (Advances in Water Resources, 2026)

Evolution of honey authentication and traceability: From conventional assays to intelligent systems integrating multi-omics and machine/deep learning for sustainable apiculture - Yingran Tang; Yuying Zhu; Enning Zhou; Gang Chen; Liming Wu; Qiangqiang Li (Trends in Food Science & Technology, 2026)

The AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED gene promotes somatic embryogenesis and polyploidy formation in Liriodendron hybrids - Yao Tang; Qi Zhao; Jinshu Li; Dingjie Yang; Lu Lu; Zhaodong Hao; Liming Yang; Tielong Cheng; Jisen Shi; Ying Chen; Jinhui Chen (Plant Cell Reports, 2026)

Effect of water salinity on the soil freezing-thawing characteristic curve of sandy soils - Yandi Wu; Anh Minh Tang; Jean-Michel Pereira; Rahima Sidi-Boulenouar; Christelle Tabbiche; Liming Hu (Journal of Hydrology, 2026)

Integrated network toxicology and transcriptomics analysis reveals the pathogenic mechanisms in DBP/MBP-induced MASLD/MASH - Haoran Li; Zhigang Chen; Yi Sun; Yicheng Jiang; Qi Liu; Yuancheng Shao; Xihan Gu; Haoyu Guan; Liming Tang (Food and Chemical Toxicology, 2026)

Addressing land-use conflicts in port cities: A diagnostic and governance framework - Qingchun Guan; Yifan Wang; Liming Liu; Chengyang Guan; Tongyu Gong; Xiaoxue Tang; Peijia Ji; Kehao Guo (Ocean & Coastal Management, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Concomitant exposure to residential greenness, nitrogen dioxide, and outdoor light at night in association with incident anxiety - Jiayun Zhang; Yexiang Sun; Zihan Li; Lisha Xu; Jingjing Hu; Jie Qiu; Xinhan Zhang; Zongming Yang; Zhanghang Zhu; Yonghao Wu; Yixing Wang; Hongbo Lin; et al. (Landscape and Urban Planning, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Quantitative study on the local structure and macroscopic property correlations in binary lithium germanate melts - Yufan Zhao; Han Sun; Jinglin You; Jiawen Lu; Jian Yang; Jiansheng Geng; Xiang Xia; Guopeng Liu; Kai Tang; Liming Lu; Qingli Zhang; Songming Wan (Chemical Engineering Journal, 2026)

Hydromorphological adjustment and river–lake disconnection in the Jingjiang Reach under long-term regulation of three Gorges Reservoir - Wenguang Luo; Yancheng Han; Liming Yan; Jun Xia; Guoqiang Tang (Geomorphology, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Real-time Monitoring Unveils Three Distinct Neuronal Response Patterns to SAW Ultrasound via L-type Calcium Channels - Yiming Chen; Wenxu Tang; Yifan Wang; Ya Gao; Jiaqi Hu; Yixuan Lu; Long Meng; Hairong Zheng; Yi Feng; Liming Cheng; Wenyong Fan; Qian Cheng; et al. (Neuroscience Bulletin, 2026)

Identification of Mitochondria-Related Genes Associated with Stroke Risk Through Multi-omics Summary Data-Based MR Analysis - Xiaorong Tang; Guannan Cheng; Siyun Chen; Lulu Yao; Liming Lu; Chenwei Shen; Lubao Feng; Wenwen Zhang; Nenggui Xu; Lin Wang (Molecular Neurobiology, 2026)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Design and synthesis of bis(indolyl)-hydrazide-hydrazone derivatives and their antifungal activities against plant pathogen fungi - Haowei Huang; Jinrui Tang; Kunrong Dang; Jiayue Tang; Enxian Li; Liming Fan; Min Ye; Guoxing Wu; Fawu Su (Natural Product Research, 2025)

Microbial metabolisms determine soil priming effect induced by organic inputs - Yingyi Fu; Wanling Liu; Zhiyi Chen; Marc Redmile-Gordon; Chao Liang; Caixian Tang; Georg Guggenberger; Shaobin Yan; Liming Yin; Jingjing Peng; Lukas Van Zwieten; Peng Wang; et al. (Soil Biology and Biochemistry, 2025)

Silicon enhanced phytoextraction of Sedum alfredii Hance by improving growth, Cd tolerance, and remolding rhizospheric properties - Junlong Xu; Yudie Shao; Xinhao Rao; Jinliang Tang; Christopher Rensing; Hend Alwathnani; Madeha Ayed Alonazi; Jinlin Zhang; Liming Zhang; Shihe Xing; Wenhao Yang (Plant and Soil, 2025)

Mannitol: A novel chemical marker in stingless bee honey - Yandong Xu; Xing Zheng; Benyan Tang; Xiaorong Yang; Patricia Vit; Milena Popova; Vassya Bankova; Liming Wu; Kai Wang (Food Chemistry, 2025)

Fracture process of a simplified laboratory model for a cross-fault tunnel with rigid reinforcement rings: Experimental and numerical insights - Liming Tang; Chun’an Tang; Lei Cheng; Wenshuo Duan; Xu Chen; Qiang Liu (Tunnelling and Underground Space Technology, 2025)

Association of residential greenness and sleep duration in adults: A prospective cohort study in China - Jiayi Li; Yaoyao Lin; Zongming Yang; Joachim Heinrich; Tianyu Zhao; Zhebin Yu; Wenqing Wang; Kaixuan Yang; Peng Shen; Hongbo Lin; Liming Shui; Jianbing Wang; et al. (Environmental Research, 2025)

Microglia Promote Lymphangiogenesis Around the Spinal Cord Through VEGF-C/VEGFR3-Dependent Autophagy and Polarization After Acute Spinal Cord Injury - Yeyang Xian; Jie Liu; Mengxuan Dai; Wensheng Zhang; Minye He; Zhengnong Wei; Yutao Jiang; Shiyong Le; Zhuoang Lin; Shuai Tang; Yunfei Zhou; Liming Dong; et al. (Molecular Neurobiology, 2025)

Sensitive shrubland and unique urbanization patterns: the key to understanding emerging towns growth in arid regions - Qi Zhang; Junling He; Chunying Ren; Cun Chang; Wenxi Tang; Xifeng Ju; Adilai Saitiniyaz; Xin Guo; Liyang Cui; Liming Liu (Environmental Monitoring and Assessment, 2025)

Vegetation and environmental changes on the Northeast China Plain during warm periods since MIS 3 - Liming Xu; Zhipeng Li; Pai Yue; Weijie Tang; Yiren Liu; Wei Chen; Min Xu; Jinglian Ge (Review of Palaeobotany and Palynology, 2024)

Outdoor light at night, air pollution and risk of incident type 2 diabetes - Yonghao Wu; Ye Jiao; Peng Shen; Jie Qiu; Yixing Wang; Lisha Xu; Jingjing Hu; Jiayun Zhang; Zihan Li; Hongbo Lin; Zhiqin Jiang; Liming Shui; et al. (Environmental Research, 2024)

Multiple hydrogen bonding induced by semi-interpenetrating polymer network binder to enhance the electrochemical performance of sodium-ion batteries electrodes - Liming Yu; An Chen; Ruixian Tang; Fangfang Zhao; Jinjin Li; Liangming Wei (Chemical Engineering Journal, 2024)

Chemical composition, odor characteristics and risk value analysis of odorants in particleboards - Fang Yang; Xianwu Zou; Liming Zhu; Bin Lv; Yuejin Fu; Bo Liu; Lina Tang; Qian Chen (Atmospheric Pollution Research, 2024)

Macrophage activation syndrome in Sepsis: from pathogenesis to clinical management - Shunyao Chen; Cong Zhang; Jialiu Luo; Zhiqiang Lin; Teding Chang; Liming Dong; Deng Chen; Zhao-Hui Tang (Inflammation Research, 2024)

Coupling rare-earth metal introduction and alkali oxide addition to achieve efficient regeneration of LiBH4 by reacting hydrous LiBO2 with Al - Yongyang Zhu; Liming Zeng; Daifeng Wu; Renheng Tang; Qing Zhou (Chemical Engineering Journal, 2024)

Contamination profile and hazards of neonicotinoid insecticides in honey from apiaries in Beijing, China - Yuan Huang; Benyan Tang; Liming Wu; Chongbo Liang; John P. Giesy; Wanli Li; Yandong Xu; Kai Wang; John R. Purdy; Keith R. Solomon; Suzhen Qi (Environmental Science and Pollution Research, 2024)

Evaluating drought stress response of poplar seedlings using a proximal sensing platform via multi-parameter phenotyping and two-stage machine learning - Xuexing Fan; Huichun Zhang; Lei Zhou; Liming Bian; Xiuliang Jin; Luozhong Tang; Yufeng Ge (Computers and Electronics in Agriculture, 2024)

Reprogramming protein stability in Escherichia coli to improve four-carbon dicarboxylic acids production - Jingyu Pan; Yongsheng Tang; Jia Liu; Cong Gao; Wei Song; Jing Wu; Liming Liu; Xiulai Chen (Chemical Engineering Journal, 2024)

Effects of uranium mining on the rhizospheric bacterial communities of three local plants on the Qinghai-Tibet Plateau - Yuanmou Tang; Xiaodie Chen; Liming Hou; Jing He; Ajia Sha; Liang Zou; Lianxin Peng; Qiang Li (Environmental Science and Pollution Research, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Cr and N co-doped biochar driving controllable peroxydisulfate activation pathways to degrade tetracycline: Pyrrolic N inducing singlet oxygen generation - Lijun Guo; Liming Zhao; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

Climate change brings both opportunities and challenges to rural revitalization in China: Evidence from apple geographical indication predictions - Yongquan Lu; Guilin Liu; Yuyang Xian; Jiaqi Tang; Liming Zhong (Agricultural Systems, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Adipocyte-derived exosomes promote the progression of triple-negative breast cancer through circCRIM1-dependent OGA activation - Yuehua Li; Baohong Jiang; Lijun Zeng; Yuanbin Tang; Xiaowen Qi; Zhixing Wan; Wenjie Feng; Liming Xie; Rongfang He; Hongbo Zhu; Yimou Wu (Environmental Research, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

Targeted Metabolomic Analysis of the Eye Tissue of Triple Transgenic Alzheimer’s Disease Mice at an Early Pathological Stage - Liming Shen; Xiaoxiao Tang; Huajie Zhang; Hongbin Zhuang; Jing Lin; Yuxi Zhao; Xukun Liu (Molecular Neurobiology, 2023)

A Systematic Investigation of Complement and Coagulation-Related Protein in Autism Spectrum Disorder Using Multiple Reaction Monitoring Technology - Xueshan Cao; Xiaoxiao Tang; Chengyun Feng; Jing Lin; Huajie Zhang; Qiong Liu; Qihong Zheng; Hongbin Zhuang; Xukun Liu; Haiying Li; Naseer Ullah Khan; Liming Shen (Neuroscience Bulletin, 2023)

Real-Time Processing and High-Quality Imaging of Navigation Strip Data Using SSS Based on AUVs - Yulin Tang; Junsen Wang; Shaohua Jin; Jianhu Zhao; Liming Wang; Gang Bian; Xinyang Zhao (Journal of Marine Science and Engineering, 2023)
In light of the prevailing approach in which data from side-scan sonar (SSS) from Autonomous Underwater Vehicles (AUVs) are primarily processed and visualized post mission, failing to meet the requirements in terms of timeliness for on-the-fly image acquisition, this paper introduces a novel method for real-time processing and superior imaging of navigation strip data from SSS aboard AUVs. Initially, a comprehensive description of the real-time processing sequence is provided, encompassing the integration of multi-source navigation data using Kalman filtering, and high-pass filtering of attitude and heading data to exclude anomalies, as well as the use of bidirectional filtering techniques within and between pings, ensuring real-time quality control of raw data. In addition, this study adopts the semantic segmentation Unet network for automatic real-time tracking of seafloor lines, devises a real-time correction strategy for radial distortion based on historical echo data, and utilizes the alternating direction multiplier method for real-time noise reduction in strip images. With the combined application of these four pivotal techniques, we adeptly address the primary challenges in real-time navigation data processing. In conclusion, marine tests conducted in Bohai Bay substantiate the efficacy of the methodologies delineated in this research, offering a fresh paradigm for real-time processing and superior visualization of SSS navigation strip data on AUVs.

Improving the performance of alkali-activated slag mortar with electro/chemically treated carbon fiber textile - Liming Huang; Luping Tang; Angelika Bachinger; Yongqiang Li; Zhenghong Yang (Journal of Cleaner Production, 2023)

Study on the Mechanism of Arsenic-Induced Lung Injury Based on SWATH Proteomics Technology - Yi Wang; Jun Zhang; Xinglai Zhang; Huajie Zhang; Xueshan Cao; Ting Hu; Jing Lin; Xiaoxiao Tang; Xiaolu Chen; Yuxuan Jiang; Xi Yan; Hongbin Zhuang; et al. (Biological Trace Element Research, 2023)

Identification of a novel prognostic signature composed of 3 cuproptosis-related transcription factors in colon adenocarcinoma - Lei Zhou; Yuwan Zhang; Yixin Xu; Tao Jiang; Liming Tang (Genes & Genomics, 2023)

Residential greenness, air pollution and incident neurodegenerative disease: A cohort study in China - Zhanghang Zhu; Zongming Yang; Luhua Yu; Lisha Xu; Yonghao Wu; Xinhan Zhang; Peng Shen; Hongbo Lin; Liming Shui; Mengling Tang; Mingjuan Jin; Jianbing Wang; et al. (Science of The Total Environment, 2023)

Transcriptional regulation of MbACO2-mediated ethylene synthesis during postharvest banana ripening - Yuqi Tang; Yan Yan; Weiwei Tie; Xiaoxue Ye; Liwang Zeng; Liming Zeng; Jinghao Yang; Biyu Xu; Meiying Li; Yu Wang; Zhengnan Xie; Zhiqiang Jin; et al. (Postharvest Biology and Technology, 2023)

Selective capture of palladium by protonation-armed pyridine nitrogen in extreme water environments - Dewei Li; Lei Zhou; Min Li; Jifeng Yang; Ziwei Yao; Li Zhang; Zhu Meng; Liming Yang; Hui Shi; Huan Tang; Xubiao Luo; Shenglian Luo; et al. (Chemical Engineering Journal, 2023)

Effects of four hormones on the mitigation of ovarian damage in tilapia (Oreochromis niloticus) after copper and cadmium exposure - Yijie Wu; Ting Huang; Xin Yan; Jun Xiao; Zhirui Ma; Liming Luo; Liting Chen; Jinling Cao; Zhanyang Tang; Xinxian Wei; Fuyan Chen; Yu Zhu; et al. (Aquatic Toxicology, 2023)

AUV-Based Side-Scan Sonar Real-Time Method for Underwater-Target Detection - Yulin Tang; Liming Wang; Shaohua Jin; Jianhu Zhao; Chao Huang; Yongcan Yu (Journal of Marine Science and Engineering, 2023)
The limitations of underwater acoustic communications mean that the side-scan sonar data of an autonomous underwater vehicle (AUV) cannot be transmitted back and processed in real time, which means that targets cannot be detected in real time. To address the problem, this paper proposes an autonomous underwater vehicle-based side-scan sonar real-time detection method for underwater targets. First, the paper describes the system and operation of real-time underwater-target detection by the side-scan sonar mounted on the autonomous underwater vehicle. Next, it proposes a real-time processing method for side-scan sonar data, method for constructing a deep-learning-based underwater-target detection model, and real-time method for underwater-target detection based on navigation strip images, which, together, solve the three key technical problems of real-time data processing, deep-learning-based detection model construction, and real-time target detection based on the autonomous underwater vehicle. Finally, through sea-based experiments, the effectiveness of the proposed methods is evaluated, providing a new solution for the autonomous underwater vehicle-based side-scan sonar real-time detection of underwater targets.

Chrome shaving-derived biochar as efficient persulfate activator: Ti-induced charge distribution modulation for 1O2 dominated nonradical process - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Science of The Total Environment, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Highly symmetric Lewis base coordinated with Sn2+ for reducing voltage loss and retarding oxidation in tin-halide perovskite solar cells - Junke Liu; Shurong Wang; Weike Zhu; Zhiyue Tang; Liming Ding; Feng Hao (Chemical Engineering Journal, 2023)

Growth Performance of Complete Diallel Crosses Among New Varieties of Chinese Pearl Oyster Pinctada martensii - Chao Fan; Xuekai Zhang; Xingzhi Zhang; Shaobo Yue; Yangchun Li; Liming Tang; Qiongzhen Li; Zhaoping Wang (Journal of Ocean University of China, 2023)

Human kidney organoids model of Esculentoside A nephrotoxicity to investigate the role of epithelial-mesenchymal transition via STING signaling - Shuyi Gu; Gaosong Wu; Dong Lu; Yu Wang; Liming Tang; Weidong Zhang (Toxicology Letters, 2023)

Gas exchange-driven carbothermal reduction for simultaneous lithium extraction from anode and cathode scraps - Yufan Zheng; Penghui Shao; Liming Yang; Yong Huang; Hong Zhang; Lili Fang; Caiting Qiu; Huan Tang; Jiachuang Shao; Xubiao Luo (Resources, Conservation and Recycling, 2023)

Construction of novel Heat-conducting Cu-based MOF nanocomposite (HK-mBNNS/PVDF) film for highly efficient Ad-/desorption of toluene - Junjie Li; Liming Liu; Syed Jalil Shah; Ying Tang; Shanliang Jiang; Guangyuan Mu; Quanru Man; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2023)

Peroxydisulfate activation using Fe, Co co-doped biochar and synergistic effects on tetracycline degradation - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2023)

Organic photovoltaic cells offer ultrahigh VOC of ∼ 1.2 V under AM 1.5G light and a high efficiency of 21.2 % under indoor light - Zongtao Wang; Ailing Tang; Helin Wang; Qiang Guo; Qing Guo; Xiangnan Sun; Zuo Xiao; Liming Ding; Erjun Zhou (Chemical Engineering Journal, 2023)

Wellbore collapse caused by thermo-chemical coupling effects drilling in shale formation - Hu Yin; Zhiqiang Tang; Liming Dai; Hao Peng (Arabian Journal of Geosciences, 2022)

A Combined Proteomics and Metabolomics Profiling to Investigate the Genetic Heterogeneity of Autistic Children - Liming Shen; Huajie Zhang; Jing Lin; Yan Gao; Margy Chen; Naseer Ullah Khan; Xiaoxiao Tang; Qi Hong; Chengyun Feng; Yuxi Zhao; Xueshan Cao (Molecular Neurobiology, 2022)

Improving succinate production by engineering oxygen-dependent dynamic pathway regulation in Escherichia coli - Cong Gao; Wenxiu Tang; Liang Guo; Guipeng Hu; Jia Liu; Liming Liu; Xiulai Chen (Systems Microbiology and Biomanufacturing, 2022)

Study on the Effect of Mass Selection and Hybridization on Growth Performance of Chinese Pearl Oyster Pinctada martensii - Chao Fan; Xuekai Zhang; Liming Tang; Xingzhi Zhang; Jinlong Li; Yangchun Li; Qiongzhen Li; Zhaoping Wang (Frontiers in Marine Science, 2022)
The pearl oyster Pinctada martensii is an important species for sea pearl production in China. To explore the influence of the combination of mass selection and hybridization on growth performance of P. martensii , we established four selected groups and four control groups (each with two within-family crosses and two reciprocal hybrid crosses) using 1-year-old offspring of two families (Family A and Family B) from Beihai, Guangxi Province, China. Generally, the growth of the selected group was greater than that of the control group for both within-family crosses and reciprocal hybrid crosses. Shell length and width were affected by genotype, environmental factors, and the interaction between the two on Days 210 and 360. The shell widths of the four reciprocal hybrid crosses all showed heterosis on Day 360. The four within-family crosses showed a certain degree of inbreeding depression during the growth period. On Day 360, the three genetic parameters for shell width of the selected group of ♀ Family B and ♂ Family A were the largest, with values of 0.70, 1.17, and 0.06 for realized heritability, standard response to selection, and current genetic gain, respectively. Overall, the growth performance of ♀ Family B × ♂ Family A in the selected group was the best. Therefore, the combination of mass selection and hybridization could be an effective way to improve the growth performance of P. martensii .

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

Theoretical and numerical models of rock wing crack subjected to hydraulic pressure and far-field stresses - Yanlin Zhao; Qiang Liu; Jian Liao; Yixian Wang; Liming Tang (Arabian Journal of Geosciences, 2020)

The compressive-shear fracture strength of rock containing water based on Druker-Prager failure criterion - Yanlin Zhao; Yixian Wang; Liming Tang (Arabian Journal of Geosciences, 2019)

The Micro Damage Model of the Cracked Rock Considering Seepage Pressure - Yanlin Zhao; Liming Tang; Qiang Liu; Senlin Xie (Geotechnical and Geological Engineering, 2019)

Diallyl trisulfide ameliorates myocardial ischemia–reperfusion injury by reducing oxidative stress and endoplasmic reticulum stress-mediated apoptosis in type 1 diabetic rats: role of SIRT1 activation - Liming Yu; Shu Li; Xinlong Tang; Zhi Li; Jian Zhang; Xiaodong Xue; Jinsong Han; Yu Liu; Yuji Zhang; Yong Zhang; Yinli Xu; Yang Yang; et al. (Apoptosis, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

RETRACTED ARTICLE: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2017)

Minocycline Attenuates Neonatal Germinal-Matrix-Hemorrhage-Induced Neuroinflammation and Brain Edema by Activating Cannabinoid Receptor 2 - Jun Tang; Qianwei Chen; Jing Guo; Liming Yang; Yihao Tao; Lin Li; Hongping Miao; Hua Feng; Zhi Chen; Gang Zhu (Molecular Neurobiology, 2016)

A Cannabinoid Receptor 2 Agonist Prevents Thrombin-Induced Blood–Brain Barrier Damage via the Inhibition of Microglial Activation and Matrix Metalloproteinase Expression in Rats - Lin Li; Yihao Tao; Jun Tang; Qianwei Chen; Yang Yang; Zhou Feng; Yujie Chen; Liming Yang; Yunfeng Yang; Gang Zhu; Hua Feng; Zhi Chen (Translational Stroke Research, 2015)

microRNA-124 inhibits proliferation and induces apoptosis by directly repressing EZH2 in gastric cancer - Liming Xie; Zhiwei Zhang; Zhiqin Tan; Rongfang He; Xi Zeng; Yuanjie Xie; Suyun Li; Guohua Tang; Hailin Tang; Xiusheng He (Molecular and Cellular Biochemistry, 2014)

IL-15 receptor alpha rs2228059 A>C polymorphism was associated with a decreased risk of esophageal cancer in a Chinese population - Jun Yin; Liming Wang; Yijun Shi; Aizhong Shao; Weifeng Tang; Xu Wang; Wenbo Zhang; Guowen Ding; Chao Liu; Yijang Chen; Suocheng Chen; Haiyong Gu (Molecular Biology Reports, 2014)

Caspase8 rs1035142 G>T polymorphism was associated with an increased risk of esophageal cancer in a Chinese population - Jun Yin; Weifeng Tang; Aizhong Shao; Liming Wang; Xu Wang; Guowen Ding; Chao Liu; Yijang Chen; Suocheng Chen; Haiyong Gu (Molecular Biology Reports, 2014)

miR-185 is an independent prognosis factor and suppresses tumor metastasis in gastric cancer - Zhiqin Tan; Hao Jiang; Youhua Wu; Liming Xie; Wenxiang Dai; Hailin Tang; Sanyuan Tang (Molecular and Cellular Biochemistry, 2014)

Neuroprotective Effect of Atorvastatin Involves Suppression of TNF-α and Upregulation of IL-10 in a Rat Model of Intracerebral Hemorrhage - Tu Ewen; Liu Qiuting; Tang Chaogang; Tang Tao; Wu Jun; Tan Liming; Xiang Guanghong (Cell Biochemistry and Biophysics, 2013)

Time-series modeling and prediction of global monthly absolute temperature for environmental decision making - Liming Ye; Guixia Yang; Eric Van Ranst; Huajun Tang (Advances in Atmospheric Sciences, 2013)
A generalized, structural, time series modeling framework was developed to analyze the monthly records of absolute surface temperature, one of the most important environmental parameters, using a deterministicstochastic combined (DSC) approach. Although the development of the framework was based on the characterization of the variation patterns of a global dataset, the methodology could be applied to any monthly absolute temperature record. Deterministic processes were used to characterize the variation patterns of the global trend and the cyclic oscillations of the temperature signal, involving polynomial functions and the Fourier method, respectively, while stochastic processes were employed to account for any remaining patterns in the temperature signal, involving seasonal autoregressive integrated moving average (SARIMA) models. A prediction of the monthly global surface temperature during the second decade of the 21st century using the DSC model shows that the global temperature will likely continue to rise at twice the average rate of the past 150 years. The evaluation of prediction accuracy shows that DSC models perform systematically well against selected models of other authors, suggesting that DSC models, when coupled with other ecoenvironmental models, can be used as a supplemental tool for short-term (∼10-year) environmental planning and decision making.

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of wetland degradation on bacterial community in the Zoige Wetland of Qinghai-Tibetan Plateau (China) - Jie Tang; Xiang Ding; Liming Wang; Qingrui Xu; Zhirong Yang; Jian Zhao; Qun Sun; Su Feng; Jie Zhang (World Journal of Microbiology and Biotechnology, 2012)

Arbuscular mycorrhizal mediation of biomass–density relationship of Medicago sativa L. under two water conditions in a field experiment - Qian Zhang; Liming Xu; Jianjun Tang; Minge Bai; Xin Chen (Mycorrhiza, 2011)